IMPACT OF TOXIC SEDIMENT ON BIOCHEMICAL ASPECT OF GPT AND GOT OF CHANNA PUNCTATUS - DR. KALPANA VERMA NARAYANKAR (International Journal of Innovations in Engineering Research and Technology, 2021)
In this study we procured toxic sediment from Amlakhadi water channel in Bhuj where paper, dye and textile industries were dumping their toxic wastes. We took Channa punctatus to test the toxicity of the sediment in the lab to find the NOEC for their GPT and GOT.